Examining outcomes of marketing actions from customer, investor, and operational perspectives - LIM, Leon Gim (Institutional Knowledge at Singapore Management University, 2018)
This dissertation examines the impact of three distinct marketing actions from three different perspectives, i.e., customer, investor, and operational. Specifically, the first essay examines investors’ evaluation of firms’ price-increase preannouncements, thereby responding to recent calls for exploring investors’ evaluation of a firm’s pricing actions which have been predominantly examined from consumers’ perspective. The second essay adopts an operations lens to present the first empirical examination about the impact of customer satisfaction on the future costs of selling and producing for a firm. The essay, therefore, is of direct importance to CEOs as they consider costs as their top priority. In addition, it is responsive to recent calls for more research on the cost implications of marketing actions. Finally, the third essay integrates the customer, investor and operational perspectives, to explore the consequences of mergers and acquisitions using a stakeholder-specific approach. Specifically, using a longitudinal dataset, this essay examines how mergers and acquisitions in the airline industry have an impact on key stakeholders – consumers, employees, senior managers, and investors. Taken together, this dissertation seeks to contribute to existing literature by exploring, for different stakeholders, the outcomes of marketing actions that have high managerial relevance, but have received little attention in current literature.